2020
DOI: 10.1002/symb.511
|View full text |Cite
|
Sign up to set email alerts
|

“It's Not a Pattern of Behavior”: Proxy Deflection of Eviction Stigma by Community Care Providers

Abstract: Community care is the “hospital without walls” model of mental health services that deinstitutionalized mental patients in the late‐twentieth century. Neoliberal reforms have challenged the implementation of community care by restricting access to permanent housing. Extreme poverty has rendered eviction commonplace for community care recipients. The mark of an eviction limits lease attainment. As a result, community care providers practice proxy deflection—redemption, externalization, and paternalism—to resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…For example, many studies have shown how different stigmatized groups engage in passive acceptance of their stigma, including withdrawing from perceived stigmatizing interactions and situations, stopping stigmatized behavior, concealing or denying stigmatizing attributes, and isolating themselves (see e.g., Meisenbach 2010 for review). Other strategies that scholar have identified include the use of humor (Lash 2022; Roschelle and Kaufman 2004), evasion of responsibility, reducing offensiveness through refocusing or minimization (Ashforth et al 2007), and active resistance (Grainger 2021; Roschelle and Kaufman 2004).…”
Section: Parental Stigma Coping and Defensesmentioning
confidence: 99%
“…For example, many studies have shown how different stigmatized groups engage in passive acceptance of their stigma, including withdrawing from perceived stigmatizing interactions and situations, stopping stigmatized behavior, concealing or denying stigmatizing attributes, and isolating themselves (see e.g., Meisenbach 2010 for review). Other strategies that scholar have identified include the use of humor (Lash 2022; Roschelle and Kaufman 2004), evasion of responsibility, reducing offensiveness through refocusing or minimization (Ashforth et al 2007), and active resistance (Grainger 2021; Roschelle and Kaufman 2004).…”
Section: Parental Stigma Coping and Defensesmentioning
confidence: 99%
“…An apartment lease is a protracted legal contract that exposes the lessee and leaser to opportunism. Landlords manage transaction costs by adopting screening criteria to select reliable tenants and solicit third‐party mediation to evict delinquent renters (Garboden and Rosen 2019; Grainger 2020; Greif 2018). Housing First providers mediate lease formation by conducting housing searches, negotiating lease applications, monitoring lease compliance, and mitigating landlord‐tenant conflict (Tsemberis 2010).…”
Section: Yielding Return On Housing First Through Micro‐economizationmentioning
confidence: 99%
“…Recent studies detail criteria that landlords use to judge applicants. Grainger (2020) demonstrates landlords interpret past evictions as evidence an applicant lacks integrity to be a responsible tenant. Electronic public records enable landlords to quickly access information about the criminal history of lease applicants (Uggen and Stewart 2015).…”
Section: Micro‐economization Of Homeless Bodies By Housing First Prov...mentioning
confidence: 99%